Applied geography - application of Geographic Information Systems (GIS) and Analytic Hierarchy Process (AHP) in agriculture through the example of winemaking, viticulture and wine tourism in Serbia. - Jovanovic, Radmila (My University, 2024)
What does a geographer do? The geographer is interested in the spatial distribution of viticulture: location, grape varieties, nature and geographical environment, cultural characteristics of the local population, economic, social and political structure of the area. For the factors of viticulture development: climate, terrain topography (slope, exposure, altitude), soil fertility and composition, human influence on the development of viticulture, market opportunities (sales, placement of goods on the market) and demand (buyers' interest in wine), use modern techniques and technologies in viticulture. The tradition of viticulture in Serbia - The earliest cultivation of vines began 7000 years ago between the Caspian Lake and the Black Sea. - On the Balkan Peninsula, the development of viticulture began before Christ. Later, the Greeks and Romans (III and IV centuries) played a major role. - Slavic tribes also continued the tradition of growing vines during the 5th and 6th centuries. - During the rule of the Turks, viticulture on the territory of Serbia stagnated. - During the Austro-Hungarian rule, organized wine production began in Serbia (various, joint factory associations, joint plantations were formed). In this period, the export of wine from Serbia to the world market (France, Germany, Russia, Romania, etc.) begins.
Keywords: Sistemas de información geográfica; Turismo - Serbia; Vinicultura - Serbia; Enoturismo; Serbia; SIG; GIS; Viticultura